What Does a Transformative Lens Bring to Credible Evidence in Mixed Methods Evaluations?. Issue 138 (6th June 2013) - Mertens, Donna M.
Abstract: Credibility in evaluation is a multifaceted concept that involves consideration of diverse stakeholders' perspectives and purposes. The use of a transformative lens is proposed as a means to bringing issues of social justice and human rights to the foreground in decisions about methodology, credibility of evidence, and use of evaluation findings. © Wiley Periodicals, Inc., and the American Evaluation Association .